The Essential Guide to Flash Games Building Interactive Entertainment with ActionScript 3.0 - Fulton, Jeff. (Apress, 2010)
The Essential Guide to Flash Games is a unique tool for Flash game developers. Rather than focusing on a bunch of low-level how-to material, this book dives straight into building games. The book is divided into specific game genre projects, covering everything from old classics such as a Missile Command-style game, to hot new genres such as retro evolved. The chapters build in complexity through the book, and new tools are introduced along the way that can be reused for other games. The game projects covered start simple and increase in complexity as more and more tools are added to your tool chest. Ten full game projects are discussed in detail. Each solves a very different game development problem and builds on the knowledge gained from the previous project. Many advanced game development techniques are covered, including particle systems, advanced controls, artificial intelligence, blitting, scrolling, and more.